Factors related to inhibition of lactation by pharmacological means at birth in a Spanish referral hospital (2011-2017) - Anna Llupià; Isabel Torà; Alba Lladó; Teresa Cobo; Josep Miquel Sotoca; Joaquim Puig (Elsevier, 2022)
Objective: To describe the maternal, neonatal and pregnancy characteristics related to inhibition of lactation (IL) with cabergoline. Method: We assessed 20,965 occasions of breastfeeding initiation, according to data collected from obstetric records at the Hospital Clinic of Barcelona (Spain) between January 2011 and December 2017. Results: IL decreased over the study period from 8.78% to 6.18% (odds ratio [OR]: 0.93 per year; 95% confidence interval [95%CI]: 0.90-0.95). Women with a lower educational level (OR: 2.5; 95%CI: 2.0-3.0), mothers living in more depressed areas (OR: 1.08 per 10 extra points over 100; 95%CI: 1.04-1.12), smokers (OR: 2.2; 95%CI: 1.9-2.6), and those with more children (OR: 1.2 for each sibling; 95%CI: 1.1-1.3), preterm birth (OR: 1.8; 95%CI: 1.4-2.3), multiple births (OR: 1.6; 95%CI: 1.2-2.1) and a higher risk pregnancy (OR: 1.3 per risk point; 95%CI: 1.2-1.4) showed a higher prevalence of IL. Compared to women born in Spain, IL was less likely in all other women with the exception of Chinese women (OR: 7.0; 95%CI: 5.7-8.6). These disparities remained during the study period. Conclusions: Factors related to lower socioeconomic status and poor health were more likely to be associated with IL. The overall use of cabergoline decreased during the study period while inequalities persisted. Taking these inequalities into account is the first step to addressing them. Resumen: Objetivo: Describir las características maternas, neonatales y del embarazo relacionadas con la inhibición de la lactancia (IL) con cabergolina. Método: Se evaluaron 20.965 ocasiones de inicio de lactancia, según los registros obstétricos del Hospital Clínic de Barcelona (2011-2017). Resultados: La IL disminuyó durante el periodo de estudio del 8,78% al 6,18% (odds ratio [OR]: 0,93 anual; intervalo de confianza del 95% [IC95%]: 0,90-0,95). Las mujeres con menor nivel educativo (OR: 2,5; IC95%: 2,0-3,0), las madres que viven en áreas más deprivadas (OR: 1,08 por 10 puntos extra sobre 100; IC95%: 1,04-1,12), las fumadoras (OR: 2,2; IC95%: 1,9-2,6), las que tienen más hijos (OR: 1,2 por cada hermano; IC95%: 1,1-1,3), los nacimientos prematuros (OR: 1,8; IC95%: 1,4-2,3), los nacimientos múltiples (OR: 1,6; IC95%: 1,2-2,1) y los embarazos de mayor riesgo (OR: 1,3 por punto de riesgo; IC95%: 1,2-1,4) tuvieron una mayor prevalencia de IL. Respecto a las mujeres nacidas en España, la IL fue menor que en las demás mujeres, con la excepción de las nacidas en China (OR: 7,0; IC95%: 5,7-8,6). Estas desigualdades se mantuvieron durante el periodo de estudio. Conclusiones: Los factores relacionados con el bajo nivel socioeconómico y la mala salud tuvieron más probabilidades de estar asociados con la IL. El uso de cabergolina disminuyó durante el periodo de estudio, mientras que las desigualdades se mantuvieron. Tener en cuenta estas desigualdades es el primer paso para abordarlas.